The study of the periodicity of catastrophic spring floods on the territory of Ukraine - Ovcharuk, Valeriya Anatolievna; Prokofiev, Oleg Miloslavovich; Todorova, Olena Ivanivna; Kichuk, Natalia Sergiyvna (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2019)
Introduction. In the period of global and regional climate change in almost all the regions of our planet there is an increase in cases of extreme natural phenomena, which definitely include floods of various origin. Over the past decades, according to the Centre for Research on the Epidemiology of Disasters (CRED), in many countries of the world there has been a record high number of natural disasters which affected about 2.7 billion people, that is more than one third of the world’s population. The purpose of article is to analyze historical data and study the current state and trends in the frequency of catastrophic floods. Methods. To estimate the trends in the chronological series of the maximum runoff of rivers the methods of statistical analysis and spatial generalization have been used. Results. On the basis of literature sources and taking into account current data, frequency of flooding in the period from 900 to 2010 in the territory of Kyivan Rus and modern Ukraine has been estimated. Analyzing the results obtained, it can be noted that the largest number of floods was observed in the period from 1501 to 1600 years (11 cases), from 1601 to 1700 years (13 cases), and in the modern period from 1901 to 2000 (10 cases); 900-1000 and 1701-1800 years can be considered as the periods with the smallest number of cases. Since the beginning of the new millennium catastrophic and high floods have been observed in Europe almost every year. In order to estimate the repeatability of catastrophic floods at the rivers in Ukraine, the chronological series of the maximum runoff of spring water have been made up in accordance with the data of hydrological stations, which have the largest and preferably continuous periods of observations from their beginning until 2015 inclusive. The analysis has shown that in Ukraine the spring floods in 1932 and 1970 are classified as catastrophic. The analysis of trends in the chronological series of annual maxima in conditions of climate change showed their heterogeneity across the territory of Ukraine: on the left bank of the Dnieper and in the Siverskyi Donets basin there is a tendency towards earlier periods of snowmelt and the occurrence of the spring floods, and on the other territory, on the contrary, there is a tendency of increase in cases of winter floods instead of the spring high water. The scientific novelty of the study is determined by the use of observational data up to 2015 inclusive, and its practical significance is determined by the opportunity to use the results when justifying hydrotechnical projects in order to minimize the consequences of catastrophic floods on rivers.